AB0386 The Role That ACR Ped-30, 50, 70 Played in Evaluating the Clinical Efficacy of TNF Antagonists in the Treatment of So-Jia. (10th June 2014) - Zeng, H.; Zeng, P.; Xie, Y.; Tang, Y.; Wang, M.
Abstract : Objectives: Using the ACR Ped-30, 50, 70 to assess the clinical efficacy of tumor necrosis factor antagonist in refractory systemic juvenile idiopathic arthritis (So-JIA). Methods: Evaluate the 30 refractory SO-JIA patients that achieved TNF antagonists using ACR Ped-30, 50, 70. The evaluation will carry out after treatment of 1 month, 3 months and 6 months. Several indicators will be evulate, insist: (1) the dosage of the hormone; (2) the body temperature; (3) count of active inflammatory joint; (4) blood sedimentation (ESR) or c-reactive protein (CRP); (5) the doctors 's overall evaluation. If there are at least 3 items that with an improvement between 30% and 49%, it will be regarded that the cases' 30% clinical symptoms alleviate. If there are at least 3 items that with an improvement between 50% and 69%, the cases' 50% clinical symptoms alleviate. If there are at least 3 items that with an improvement above 70%, the cases' 70% clinical symptoms alleviate. It will be treated as poor efficacy or invalid if there are more than 3 items that with an improvement less than 29%. The occurrence of adverse reactions are monitored and recorded at the same time. Results: After 1 month's treatment, only 40% (12/30) of children achieved more than 30% of the clinical symptoms alleviated. Among them, 13.3% (4/30) achieved more than 50% of the clinical symptoms alleviated, 10% (3/30) reached more than 70% of the clinical symptoms eased. 2 cases merged with muscular stiffness, so the biological agent's treatment was stopped. After 3 month's treatment, 63% (17/27) cases achieved more than 30% of the clinical symptoms alleviated. Among them, 44.4% (12/27) achieved more than 50% of the clinical symptoms alleviated, 22.2% (6/27) reached more than 70% of the clinical symptoms eased 5 cases discontinued because of recurrent infections or the ineffective treatment; 16 cases continued treatment to 6 months Among them, 55.6% (15/27) cases achieved more than 30% clinical symptoms alleviated, 40.7% (11/27) achieved more than 50% clinical symptoms alleviated, 29.6% (8/27) reached more than 70% of the clinical symptoms eased. After 6 month, 3 cases that had more than 70% symptom in remission were recurrent because of repeated infection. 4 cases maintain biological preparation treatment up to two years, 3 of them were in stable condition, and 1 switch to other biological agents because that his bone destruction continued. Conclusions: The ACR Ped-30, 50, 70 can evaluate the clinical efficacy of tumor necrosis factor antagonists in the treatment of refractory systemic juvenile idiopathic arthritis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5476